2023
DOI: 10.1021/acs.molpharmaceut.2c00878
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis on the Effectiveness of Extracellular Vesicles as Nanosystems for Targeted Delivery of Anticancer Drugs

Abstract: While the efficacy of anticancer drugs is hampered by low bioavailability and systemic toxicity, the uncertainty remains whether encapsulation of these drugs into natural nanovesicles such as extracellular vesicles (EVs) could improve controlled drug release and efficacy for targeted tumor therapy. Thus, we performed a metaanalysis for studies reporting the efficacy of EVs as nanosystems to deliver drugs and nucleic acid, protein, and virus (NPV) to tumors using the random-effects model. The electronic search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 170 publications
0
2
0
Order By: Relevance
“…For example, chemical molecules such as doxorubicin (DOX) and paclitaxel (PAC) are commonly enclosed through incubation and sonication, whereas genetic materials like miRNA and siRNA are enclosed through transfection and electroporation. 34 Moreover, the loading efficiency is significantly affected by the hydrophobic nature of the drug given the hydrophilic nature of the exosome core.…”
Section: Approaches For Loading Cargos Into Exosomesmentioning
confidence: 99%
“…For example, chemical molecules such as doxorubicin (DOX) and paclitaxel (PAC) are commonly enclosed through incubation and sonication, whereas genetic materials like miRNA and siRNA are enclosed through transfection and electroporation. 34 Moreover, the loading efficiency is significantly affected by the hydrophobic nature of the drug given the hydrophilic nature of the exosome core.…”
Section: Approaches For Loading Cargos Into Exosomesmentioning
confidence: 99%
“…Analysis of 119 animal studies and 1 clinical study indicated marked reductions in tumor growth and improved survival rates with sEVencapsulated drugs compared to free drugs. 83 Precise drug localization at the tumor site underscores the effectiveness of sEVs as secure and efficient nanoplatforms.…”
Section: Small Evs In Cancer Drug Deliverymentioning
confidence: 99%
“…Recent seminal studies highlighted the EV potential in delivering siRNAs, small molecules, and microRNAs (Möller and Lobb, 2020). Through surface engineering and cargo loading techniques, EVs were reported to exert anti-inflammatory and antitumor effects, or neuroprotection and tissue regeneration (Muhammad et al, 2023) , (Roudi et al, 2023) , (Greening et al, 2023).…”
Section: Introductionmentioning
confidence: 99%